The Impact of Foreign Investment on Firm Performance: Indonesia After the 2007 FDI Reform - Hafiluddin, Nauval; Patunru, Arianto Arif (Economics and Finance in Indonesia, 2022)
Foreign Direct Investment (FDI) plays a crucial role in the economy of Indonesia. The new FDI law passed in 2007 serves as a new milestone in the FDI regime in Indonesia. As the country implements the new regulation, the impact of foreign investment on firm performance becomes an interesting subject. This paper aims to estimate the effect of foreign investment on the productivity and contribution of firms in relation to the new FDI law in Indonesia. This study employed a combination of Propensity Score Matching (PSM) and Difference-in-Differences (DiD) methods to eliminate endogeneity problems and to examine causality. We discover that foreign investment increases the contribution of firms in terms of tax and employment yet drives no significant change in firm productivity after the new FDI law came into force. This result implies that foreign investors might have picked already productive domestic firms; and that other firms need to increase their level of attractiveness while policymakers need to improve the investment climate in order to attract more FDI.